GLOBALIZATION AND GLOBALISM - Ороховська, Л. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Based on the analysis of globalization as a history phenomenon the article shows that this occurrence has two aspects – objective (as an aspect of social life) and subjective (as means of purposeful influence on social life).